Análise de incertezas da vazão volumétrica de gás natural relatada nas condições de referência - Mosckem, Marina Duarte (2017)
It’scommonforregulationstorequirenaturalgasflowmeasurement to be reported on a volumetricbasis. Therefore, the measurement should also be reported at a specific pressure and temperature,referred toas standard conditions. In Brazil, petroleum and gasmeasurements must comply with ANP/Inmetro Ordinance 01/2013, which states the followingstandardconditions: 1 bar, 20°C. When the flowing conditions are not the same as the standard ones, the measurement must be corrected for the standard condition bymeans of thermodynamic Equations of State –EOS. Thus, themeasurement reportedin the standard conditions carries a portion of uncertainty relative to this operation, whose value depends onthe temperature and pressure, as well as on the chosen EOS. The main goal of the work is to evaluate this parcel of the uncertainty, especially incritical flowing conditions. Some typical natural gas compositionswere selected and the following flowing conditions: 50 bar, 4°C.Results obtained by means of Monte Carlo simulationshow that the measurement reported at the standard conditions carries a portion of uncertainty generally greater than1,0percentagepoints,only due to thenecessary correction just commented. It’s a significantly high value, especially if we take into account that Brazilian regulation states a maximum of 2% for fiscal measurements, for example